Ferroptosis-associated pathological injury mechanisms and therapeutic strategies after intracerebral hemorrhage - Gong, Yuhua; Yang, Fumei; Liu, Ying; Gong, Yuping (Frontiers in Neurology, 2025)
Intracerebral hemorrhage (ICH) is an important neurological disease caused by the rupture of blood vessels in the brain parenchyma, with a high mortality and disability rate. At present, many studies have focused on the injury mechanisms and intervention strategies after ICH. However, there is no effective clinical treatment that can significantly improve the prognosis of ICH patients. Ferroptosis, a regulated form of cell death, has been identified as a significant contributor to brain tissues damage and neurological dysfunction following ICH. The hallmark of ferroptosis is iron-dependent lipid peroxidation, which is closely related to the pathological process of iron overload and oxidative stress after ICH. Exploring the interaction between ferroptosis and pathological injury mechanisms post-ICH will contribute to our understanding the key pathways involved in the ferroptosis-related injury mechanisms and facilitating the discovery of appropriate intervention strategies. On this basis, we present a comprehensive overview of ferroptosis-related brain injury mechanisms (e.g., iron overload, oxidative stress, inflammatory response and mass effect) in the pathogenesis and development of ICH. Following ICH, the degradation of hematoma and iron metabolism provide the fundamental material basis for ferroptosis, and oxidative stress primarily participates in the lipid peroxidation process of ferroptosis via related molecular pathways (such as the GPX4). By synthesizing current evidence, this article aims to provide a theoretical foundation for future research on therapeutic strategies targeting ferroptosis and related pathways in ICH.